Step * 1 1 1 of Lemma bag-drop-commutes


1. Type
2. T
3. a2 bag(T)
4. T
5. as@0 bag(T)
6. eq EqDecider(T)
7. bs bag(T)
8. ∀x,y:T.  Dec(x y ∈ T)
9. ¬(x y ∈ T)
10. ∀x:T. ∀bs:bag(T).
      ((∃as:bag(T). ((bs ({x} as) ∈ bag(T)) ∧ (bag-remove1(eq;bs;x) (inl as) ∈ (bag(T)?))))
      ∨ ((¬x ↓∈ bs) ∧ (bag-remove1(eq;bs;x) (inr ⋅ ) ∈ (bag(T)?))))
11. as bag(T)
12. bs ({x} {y} as@0) ∈ bag(T)
13. bag-remove1(eq;bs;x) (inl ({y} as@0)) ∈ (bag(T)?)
14. a1 bag(T)
15. bs ({y} {x} a2) ∈ bag(T)
16. bag-remove1(eq;bs;y) (inl ({x} a2)) ∈ (bag(T)?)
17. as ({y} as@0) ∈ bag(T)
18. bag-remove1(eq;{y} as@0;y) (inl as@0) ∈ (bag(T)?)
19. a1 ({x} a2) ∈ bag(T)
20. bag-remove1(eq;{x} a2;x) (inl a2) ∈ (bag(T)?)
⊢ as@0 a2 ∈ bag(T)
BY
(Assert ⌜({y} {x} a2) ({x} {y} as@0) ∈ bag(T)⌝⋅ THEN Auto) }

1
1. Type
2. T
3. a2 bag(T)
4. T
5. as@0 bag(T)
6. eq EqDecider(T)
7. bs bag(T)
8. ∀x,y:T.  Dec(x y ∈ T)
9. ¬(x y ∈ T)
10. ∀x:T. ∀bs:bag(T).
      ((∃as:bag(T). ((bs ({x} as) ∈ bag(T)) ∧ (bag-remove1(eq;bs;x) (inl as) ∈ (bag(T)?))))
      ∨ ((¬x ↓∈ bs) ∧ (bag-remove1(eq;bs;x) (inr ⋅ ) ∈ (bag(T)?))))
11. as bag(T)
12. bs ({x} {y} as@0) ∈ bag(T)
13. bag-remove1(eq;bs;x) (inl ({y} as@0)) ∈ (bag(T)?)
14. a1 bag(T)
15. bs ({y} {x} a2) ∈ bag(T)
16. bag-remove1(eq;bs;y) (inl ({x} a2)) ∈ (bag(T)?)
17. as ({y} as@0) ∈ bag(T)
18. bag-remove1(eq;{y} as@0;y) (inl as@0) ∈ (bag(T)?)
19. a1 ({x} a2) ∈ bag(T)
20. bag-remove1(eq;{x} a2;x) (inl a2) ∈ (bag(T)?)
21. ({y} {x} a2) ({x} {y} as@0) ∈ bag(T)
⊢ as@0 a2 ∈ bag(T)


Latex:


Latex:

1.  T  :  Type
2.  x  :  T
3.  a2  :  bag(T)
4.  y  :  T
5.  as@0  :  bag(T)
6.  eq  :  EqDecider(T)
7.  bs  :  bag(T)
8.  \mforall{}x,y:T.    Dec(x  =  y)
9.  \mneg{}(x  =  y)
10.  \mforall{}x:T.  \mforall{}bs:bag(T).
            ((\mexists{}as:bag(T).  ((bs  =  (\{x\}  +  as))  \mwedge{}  (bag-remove1(eq;bs;x)  =  (inl  as))))
            \mvee{}  ((\mneg{}x  \mdownarrow{}\mmember{}  bs)  \mwedge{}  (bag-remove1(eq;bs;x)  =  (inr  \mcdot{}  ))))
11.  as  :  bag(T)
12.  bs  =  (\{x\}  +  \{y\}  +  as@0)
13.  bag-remove1(eq;bs;x)  =  (inl  (\{y\}  +  as@0))
14.  a1  :  bag(T)
15.  bs  =  (\{y\}  +  \{x\}  +  a2)
16.  bag-remove1(eq;bs;y)  =  (inl  (\{x\}  +  a2))
17.  as  =  (\{y\}  +  as@0)
18.  bag-remove1(eq;\{y\}  +  as@0;y)  =  (inl  as@0)
19.  a1  =  (\{x\}  +  a2)
20.  bag-remove1(eq;\{x\}  +  a2;x)  =  (inl  a2)
\mvdash{}  as@0  =  a2


By


Latex:
(Assert  \mkleeneopen{}(\{y\}  +  \{x\}  +  a2)  =  (\{x\}  +  \{y\}  +  as@0)\mkleeneclose{}\mcdot{}  THEN  Auto)




Home Index